PENGELOLAAN DANA DESA DALAM UPAYA AKSELERASI PEMBERDAYAAN MASYARAKAT DESA TAHUN 2019-2020 (STUDI KASUS PADA DESA PULAU PERMAI KECAMATAN TAMBANG KABUPATEN KAMPAR) - Rahmadani Putri; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Management of Village Funds regulated in Minister of Home Affairs Regulation No. 113 of 2014 in fulfilling and implementing the administration of Pulau Permai Village requires a Village Fund budget so that it can improve village development and empower the people of Pulau Permai Village. Permai Island Community Empowerment Activities in 2019-2020 include several empowerment activities, such as: sewing training, computer training, BPD capacity building training, stunting outreach, culinary training, and talikur training. But on the other hand, the problem is that the empowerment carried out by Pulau Permai Village has no impact on the economy because the budget for empowerment is not used properly so that it has not been able to explore the potential that exists in Pulau Permai Village. This study used qualitative research methods. Data collection is done by observation, interviews and documentation. In this study, researchers used the theory according to Isbandi Rukminto Adi, there were 7 stages of empowerment consisting of: preparation stage, assessment stage, alternative program planning stage, action plan formulation stage, program implementation stage, evaluation stage, termination stage. Based on the results of data analysis and discussion that has been carried out by the authors, the authors can draw conclusions, namely: 1. Village Fund Management in Pulau Permai Village for 2019-2020 carried out as best as possible by the village government. But in the process there were several problems that occurred, starting from planning that was not mature and not optimal as a whole, namely the lack of community participation 2. The inhibiting factors for the management of the Pulau Permai Village Fund, Tambang District, Kampar Regency in 2019, are as follows: (1). Human resources, (2). Minimal community participation, (3). Facilities and infrastructure, (4). Lack of motivation and awareness of the Village community. Keywords: Village Fund, Community Empowerment